A Tool for Computation of Changes in Na+, K+, Cl− Channels and Transporters Due to Apoptosis by Data on Cell Ion and Water Content Alteration - Yurinskaya, Valentina E.; Vereninov, Igor A.; Vereninov, Alexey A. (Frontiers in Cell and Developmental Biology, 2019)
Monovalent ions are involved in a vast array of cellular processes. Their movement across the cell membrane is regulated by numerous channels and transporters. Identification of the pathways responsible for redistribution of ions and cell water in living cells is hampered by their strong interdependence. This difficulty can be overcome by computational analysis of the whole cell flux balance. Our previous computational studies were concerned with monovalent ion fluxes in cells under the conditions of balanced ion distribution or during transition processes after stopping the Na+/K+ pump. Here we analyze a more complex case – redistribution of ions during cell apoptosis when the parameters keep changing during the process. New experimental data for staurosporine-induced apoptosis of human lymphoma cells U937 have been obtained: the time course of changes in cellular K+, Na+, Cl– and water content, as well as Rb+ fluxes as a marker of the Na/K pump activity. Using a newly developed computational tool, we found that alteration of ion and water balance was associated with a 55% decrease in the Na+/K+-ATPase rate coefficient over a 4-hour period, with a time-dependent increase in potassium channel permeability, and a decrease in sodium channel permeability. The early decrease in [Cl–]i and cell volume were associated with an approximately 5-fold increase in chloride channel permeability. The developed approach and the presented executable file can be used to identify the channels and transporters responsible for alterations of cell ion and water balance not only during apoptosis but in other physiological scenarios.